Analysis of sea cucumber food habits (Holothuroidea) in Tanjung Gosale village Guraping subdistrict North Oba city Tidore Islands - Yuyun Abubakar; Fajria Dewi Salim (Jurnal Biologi Tropis, 2021)
This study aims to find out the composition of sea cucumber types in Tanjung Gosale Guraping Village, find out the composition of sea cucumber food types in Tanjung Gosale Guraping Village and determine the food habits of sea cucumber types (main food, supplements, and incidental foods) contained in the stomach contents of sea cucumbers. The research procedure is carried out measurements of the length and weight of sea cucumbers using a measuring bar and analytical scales. Then the sea cucumber is dissected to be taken by the stomach, then analyzed the food contained in the stomach. Before the stomach is dissected first done weighing the weight of the stomach using analytical scales and measurements of the length of the stomach using the bar. The stomach of sea cucumbers that have been surgically then carried out observations of the contents of the stomach per individual in a microscope to find out the types of food organisms contained in the stomach of the sea cucumber. The results showed that the composite.